Istinbāṭ al-Maqāṣid al-Syarī‘ah sebagai Metode Pemahaman Hadis Larangan Safar Perempuan tanpa Maḥram - Azhary, Muhammad Royyan Faqih; Choir, Ma’sum Ahlul; Asis, Joharis bin; Muthohharun Afif; Zubaidi, Advan Navis (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2026)
This study reconstructs the methodological hierarchy for resolving apparent contradictions (taʿāruḍ al-adillah) within Islamic legal sources. It critically argues that the theories of nasikh-mansūkh (abrogation) and tarjīḥ (preferential weighting) are often prioritized disproportionately. Through theoretical examination and in-depth case studies, this research positions both theories as ultimum remedium (last resort), while asserting harmonization (al-jamʿu) and contextualization (munsaʾ) as the primary methods. This qualitative research with a descriptive-analytical approach utilizes primary data from the works of classical and contemporary scholars. The principle is tested through three critical case studies: the controversy over abrogation claims regarding peace-war verses, claims of contradiction between mutashābih hadiths and the Qur'an, and claims of abrogation concerning the hadith about a deceased person being tormented due to their family's weeping. The analysis confirms that genuine contradiction within revelation is impossible. The three case studies prove that existing contradictions are apparent (ẓāhirī) and can be resolved through semantic harmonization and contextual understanding. For example, the relationship between peace and war verses is explained by dynamic contextualization (munsaʾ), not permanent abrogation. In the case of the hadiths, the approaches of taʾwīl (figurative interpretation) and al-jamʿu prove effective in reconciling the texts. In conclusion, nasikh-mansūkh and tarjīḥ should serve as mechanisms of last resort, to be employed only after all efforts at harmonization and contextual interpretation have been exhausted. This article offers a methodological reconstruction in uṣūl al-fiqh by providing a clear hierarchy, challenging hasty conventional applications, and advocating for a paradigm that ensures the unity and contextual wisdom of the Shari'ah.